2005
DOI: 10.1117/12.605913
|View full text |Cite
|
Sign up to set email alerts
|

Biological agent detection and identification using pattern recognition

Abstract: This paper discusses a novel approach for the automatic identification of biological agents. The essence of the approach is a combination of gene expression, microarray-based sensing, information fusion, machine learning and pattern recognition. Integration of these elements is a distinguishing aspect of the approach, leading to a number of significant advantages. Amongst them are the applicability to various agent types including bacteria, viruses, toxins, and others, ability to operate without the knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Performance studies for the above approach included identification of four pathogens including bacterial, viral, and toxin. The results of the computational experiments with the approach we developed [5] [6] indicated that, within the constraints of the data we had in that effort, high levels of identification accuracy can be obtained using that fusion approach.…”
Section: Information Fusion In Cbd: Selected Approachesmentioning
confidence: 97%
See 1 more Smart Citation
“…Performance studies for the above approach included identification of four pathogens including bacterial, viral, and toxin. The results of the computational experiments with the approach we developed [5] [6] indicated that, within the constraints of the data we had in that effort, high levels of identification accuracy can be obtained using that fusion approach.…”
Section: Information Fusion In Cbd: Selected Approachesmentioning
confidence: 97%
“…), operation without the knowledge of pathogen's genome sequence, and the potential for identification of uncataloged, i.e., emerging pathogens. The biological genomic aspects of this effort are beyond the scope of this paper and can be found in [6]. The brief sketch that follows touches only on the aspects pertinent to the information fusion topic.…”
Section: Information Fusion In Cbd: Selected Approachesmentioning
confidence: 99%